The Role of Proverbs and Sayings in the Language Learning Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the study of the role of proverbs and sayings in the language learning process. Proverbs are also known as sayings. Proverbs give some form of life advice. Every language and culture has them, and many proverbs exist in more than one language. It is important not to miss any of the words in most proverbs because the meaning can be lost if even one word is changed or left out. This list of English proverbs includes definitions and examples, and is meant to improve English vocabulary and English cultural knowledge.